Environmental judicature and firm productivity: Evidence from a quasi-natural experiment - Xiaoqi Huang; Wenbo Yao; Zhi Cao (PLoS ONE, 2025)
The impact of environmental governance on firm productivity has been widely discussed, but few studies have examined the function of environmental judicature. Using the establishment of environmental courts as a quasi-natural experiment, this paper examines the relationship between environmental judicature and firm productivity. Our findings show that environmental courts will reduce firm productivity in the short term, chiefly owing to the increased environmental violation costs, environmental reputation costs and environmental compliance costs. The conclusion remains robust after mitigation of heterogeneous treatment effects, PSM-DID estimation, placebo tests and IV estimation. This negative effect is more pronounced for firms located in regions with high legal scores and low government intervention, for firms located in the eastern region, for firms with weak market power, and for firms with high pollution intensity. In addition, our further analysis suggests that environmental courts would improve the long-term firm productivity and regional green productivity, indicating that strengthening environmental judicature are conducive to firms’ sustainable growth and regions’ green transformation in the long run.